2023
DOI: 10.1155/2023/5916294
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Percolation and Seepage Behaviors in Ion‐Adsorption‐Type Rare Earth Ore Leaching Process

Abstract: Ionic rare earth ore is a type of featured rare earth ore in China. Its mining process suffers from a long leaching cycle and considerable consumption of leaching agents. Improving mining efficiency requires a sound physical understanding of the leaching process. In this study, the CFD-based numerical model is used to analyze the physical process of leaching through porous media formed by particles. The simulation results indicate that a lower packing porosity and smaller particles packed granular porous mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Ionic rare earth mine landslide belongs to shallow landslide and small landslide, mainly concentrated in high hilly terrain areas, landslide original terrain slope angle is concentrated in the range of 20 ~ 40 degrees, and the top of the landslide is mostly located in the foothill concave slope, the landslide is located in the strongly weathered residual accumulation and granite fully weathered layer, and the rainfall has a certain synchronization, the greater the rainfall with the injection of magnesium sulfate extraction solution, the bottom of the shallow well of liquid injection and fully weathered ore layer contact The stability of the slope on the datum surface is greatly affected and becomes landslide (Dianyu et al, 2023). In this paper, we monitored the earth pressure changes and fractures of two typical steep slopes, and the results showed that the steep slopes in magnesium sulfate extract leaching are easy to produce pushing landslides in the upper slope to the gentle slope system, and on the steep slopes with uniform slope, the intensity of magnesium sulfate extract is too large in the early stage is easy to produce pushing landslides, and the slope angle, slope height, the angle and the weight of internal friction of the fully weathered layer, during the magnesium sulfate extract leaching are taken as factors affecting the stability.…”
Section: Topography In Uencementioning
confidence: 99%
“…Ionic rare earth mine landslide belongs to shallow landslide and small landslide, mainly concentrated in high hilly terrain areas, landslide original terrain slope angle is concentrated in the range of 20 ~ 40 degrees, and the top of the landslide is mostly located in the foothill concave slope, the landslide is located in the strongly weathered residual accumulation and granite fully weathered layer, and the rainfall has a certain synchronization, the greater the rainfall with the injection of magnesium sulfate extraction solution, the bottom of the shallow well of liquid injection and fully weathered ore layer contact The stability of the slope on the datum surface is greatly affected and becomes landslide (Dianyu et al, 2023). In this paper, we monitored the earth pressure changes and fractures of two typical steep slopes, and the results showed that the steep slopes in magnesium sulfate extract leaching are easy to produce pushing landslides in the upper slope to the gentle slope system, and on the steep slopes with uniform slope, the intensity of magnesium sulfate extract is too large in the early stage is easy to produce pushing landslides, and the slope angle, slope height, the angle and the weight of internal friction of the fully weathered layer, during the magnesium sulfate extract leaching are taken as factors affecting the stability.…”
Section: Topography In Uencementioning
confidence: 99%